Réponses

2012-09-18T17:55:46+02:00

a) 2(x-5)-3(x-4)=x-3

   2x -10 -3x +12 = x-3

   2x -3x -x = 10 -12 -3

   -2x = -5

   x = 5/2 = 2,5

 

b) x/2-1/3=x/4-1

    x/2 -x/4 = -1 + 1/3

    2x/4 -x/4 = -3/3 + 1/3

    -x/4 = -2/3

    -x = -8/3                          (4 fois -2 le tout sur 3 : produit en croix en gros

    x = 8/3 

 

c) 4(x+1)²-9=0

    4 (x² +2x +1) -9 = 0

    4x² +8x +4 -9 =0

     4x² +8x -5 = 0

 

SI tu as appris avec delta il s'agit d'un trinome sinon il faut factoriser par x:

    (x) (4x +8) = -5

    …………